Transition to parenthood after successful non-donor in vitro fertilisation: The effects of infertility and in vitro fertilisation on previously infertile couples' experiences of early parenthood. (July 2021) - Allan, Helen; Mounce, Ginny; Culley, Lorraine; van den Akker, Olga; Hudson, Ruth
Recent social science research in the field of parenting following assisted conception has focused on the experiences of donor-assisted conception and surrogacy. This article draws from a study which explored the experiences of the transition to early parenthood in 16 heterosexual non-donor couples and includes a specific consideration of the experiences of men as they navigate this journey. We argue that these couples' transition to early parenthood can be as complex and provisional as in other newer forms of family making as they struggle with an emerging identity as a parent after successful non-donor in vitro fertilisation following their experiences of infertility. Their family making is contingent upon their ability to work at integrating their experiences of infertility and in vitro fertilisation into their emerging identity as a parent. This struggle is prominent when they contemplate a further pregnancy. Considering a sibling causes them further uncertainty and anxiety because it reminds them of their infertile identify and the possibility of further in vitro fertilisation. We report novel findings about the experiences of this transition to parenthood: how couples' identity as parents is shaped by the losses and grief of infertility and the anxiety of in vitro fertilisation. We argue that their struggle with an emerging parenthood identity challenges the normative, naturalised view of non-donor heterosexual in vitro fertilisation parenthood. Our work contributes to the work on identity in parenthood after in vitro fertilisation in an ongoing effort to understand how assisted technologies shape infertile parents' lives. This article reports a small study with a relatively homogeneous sample recruited from one fertility clinic. Nevertheless as an exploratory study of an under researched topic, we discuss useful insights and ideas for further research with larger and more diverse samples.